Awareness and Utilization of Information and CommunicationTechnology (ICT) in Agriculture - Farmer’s perspective - R. Sendilkumar; Rakesh G. Nair; M. Israel Thomas (Journal of Agricultural Extension Management, 2025)
In recent times, Information and Communication Technology (ICT) has become relevant in the Indian agricultural sector. In this age of information technology, extension can empower the farming community with agricultural knowledge through /CT for the inclusive development of agriculture. The physical distance and logistic problems are the major impediments for extension services. In this context, strengthening extension services with effective use of JCT seems indispensable. Hence a study was conducted with an objective to know the awareness and utilization of JCT among farmer users of Aksahya e-kendra in Adat Crama Panchayat of Thrissur district, Kerala. The data were collected by administering a pre-tested, structured interview schedule. · The study reveals that the awareness regarding information provided through /CT tools was medium. The utilization of computer enabled /CT tools for seeking agricultural information was not substantial. However, the information provided through /CT tools was found to be useful to farmers and they have expressed medium level of satisfaction towards its usage. Major constraints in utilization of ICTs by the respondents were difficulty in further clarification of information, lack of location specific information, lack of awareness, and high cost of technology